Control of localization and optical properties with deep-subwavelength engineered disorder - Oh, Seunghwa; Kim, Jungmin; Piao, Xianji; Kim, Seulong; Kim, Kihong; Yu, Sunkyu; Park, Namkyoo (Optics Express, 2022)
The effect of deep subwavelength disorder in one-dimensional dichromic multilayer films on the optical transmission, localization length, and Goos–Hänchen shift around the critical angle is analyzed using sets of disordered multilayer films with different degrees of order metric τ. For each Gaussian-perturbed multilayer film designed by a Metropolis algorithm targeting the predetermined order metric τ, the numerically obtained localization length and transmission show excellent agreement with the recent theoretical analysis developed for disordered multilayer films, further revealing τ-dependence of the Goos–Hänchen shift across the critical angle. Emphasizing the role of deep subwavelength structures in disorder-induced transmission enhancement, our result thus paves the way toward the inverse design of a deep subwavelength disordered structural landscape for the targeted order metric τ or abnormal optical responses - including the Goos–Hänchen shift.
Keywords: Critical angles; Degree of ordering; Gaussians; Goos-hanchen shifts; Localisation; Localization length; Metropolis algorithms; Multilayers films; One-dimensional; Sub-wavelength